Efficacy and safety of acupuncture in the treatment of Meniere’s disease: a systematic review and meta-analysis - Tang, Mingjie; Li, Yinghong; Lu, Man; Zhang, Tianchen; Ge, Yanhao; Han, Jie; Tang, Jiqin; Chen, Zhaoming (Frontiers in Medicine, 2024)
BackgroundMeniere’s disease (MD) is an idiopathic chronic inner ear disease that seriously impacts patients’ physical and mental health. Medications may be effective for a proportion of patients, and additional effective treatments are still needed. This review aimed to evaluate the efficacy of acupuncture treatment for MD.MethodsEight databases were systematically searched from their inception to June 1, 2024, to identify randomized clinical trials on acupuncture treatment for MD. The Cochrane Risk of Bias 2.0 tool was used to assess the risk of bias in included studies, and meta-analysis was conducted by RevMan 5.4 and Stata 16.0 software.ResultsSix studies were included in this review. The treatment group received acupuncture or acupuncture combined with Western medicine, while the control group was treated with Western medicine. The treatment group was superior to the control group in terms of efficacy rate (RR: 1.20; 95% CI: 1.11–1.29; p < 0.0001). The treatment group reduced dizziness handicap inventory (DHI) (MD: 6.94; 95% CI: 1.58–12.30; p = 0.01), tinnitus handicap inventory (THI) (MD: 6.52; 95% CI: 0.77–12.27; p = 0.03), stuffy ear visual analog scale (VAS) (MD: 0.87; 95% CI: 0.54–1.20; p < 0.0001) and pure tone audiometry score (MD: 6.57; 95% CI: 5.62–7.51; p < 0.0001) to a greater degree than those of the control group. There were some methodological shortcomings in the included studies, including failure to implement blinding, inappropriate outcome measures, and heterogeneity of clinical interventions, such as selected acupoints, acupuncture sessions, and therapist techniques.ConclusionAcupuncture may improve the symptoms of vertigo, tinnitus, ear fullness and hearing loss in patients with MD. However, due to the lack of literature included in this study and methodological weaknesses like randomization, blinding, and clinical heterogeneity, more well-designed long-term follow-up RCTs are needed to evaluate the efficacy and safety of acupuncture.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/(CRD42024549261).